1987
DOI: 10.1128/aem.53.3.509-513.1987
|View full text |Cite
|
Sign up to set email alerts
|

Transport of lactate and other short-chain monocarboxylates in the yeast Saccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae IGC4072 grown in lactic acid medium transported lactate by an accumulative electroneutral proton-lactate symport with a proton-lactate stoichiometry of 1:1. The accumulation ratio measured with propionate increased with decreasing pH from ca. 24-fold at pH 6.0 to ca. 1,400-fold at pH 3.0. The symport accepted the following monocarboxylates (Km values at 25 degrees C and pH 5.5): D-lactate (0.13 mM), L-lactate (0.13 mM), pyruvate (0.34 mM), propionate (0.09 mM), and acetate (0.05 mM), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
1
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(72 citation statements)
references
References 10 publications
9
60
1
2
Order By: Relevance
“…The uptake of D-galacturonic acid was strongly enhanced at low pH, which might have been an indication for symport. However, there was only modest inhibition by the protonophores DNP and CCCP, which in the literature have been shown to inhibit symport systems completely at even lower concentrations [14,15]. In addition, we did not observe intracellular concentration of D-galacturonic acid above the extracellular substrate levels, nor a low K mvalue as has been reported previously for classical symport systems [25,26].…”
Section: Discussionsupporting
confidence: 69%
“…The uptake of D-galacturonic acid was strongly enhanced at low pH, which might have been an indication for symport. However, there was only modest inhibition by the protonophores DNP and CCCP, which in the literature have been shown to inhibit symport systems completely at even lower concentrations [14,15]. In addition, we did not observe intracellular concentration of D-galacturonic acid above the extracellular substrate levels, nor a low K mvalue as has been reported previously for classical symport systems [25,26].…”
Section: Discussionsupporting
confidence: 69%
“…However, X-gal overlay assays with cells incubated in the presence of other carbon sources (2% pyruvate, acetate, succinate and 0.1% oleic acid) did not reveal any differences in comparison to the wild-type (data not shown). Thus, none of the MCH genes is repressed by glucose or is completely dependent on the presence of lactic acid, in contrast to the reported monocarboxylate transport systems of S. cerevisiae (Cá ssio et al, 1987;Casal et al, 1995Casal et al, , 1996.…”
Section: Transcriptional Regulation Of Monocarboxylate Transporter-hocontrasting
confidence: 70%
“…The mechanisms of transport of monocarboxylic acids in S. cerevisiae have already been described for the strains IGC 4072 (Cá ssio et al, 1987;Casal et al, 1996) and W303 (Casal et al, 1995). It was also previously shown that the product of JEN1 is a permease for monocarboxylates, inducible by lactic acid .…”
Section: Uptake Of Monocarboxylate Substratesmentioning
confidence: 89%
See 1 more Smart Citation
“…The transport of monocarboxylic acids through the plasma membrane, the ¢rst step of their metabolism, has been elucidated in the strain Saccharomyces cerevisiae IGC 4072 [1,2]. Two distinct monocarboxylate carriers were found, regarding either their speci¢city or regulation.…”
Section: Introductionmentioning
confidence: 99%